PEDAGOGICAL IMPERATIVES FROM BASIC EDUCATION TEACHERS PRACTICING SUSTAINABLE LIFESTYLE IN URBAN MANILA - Wensley M. Reyes, - (2019)
A 2018 survey on sustainability ranks Manila, the Philippines' capital, among lowest in the Sustainable Cities Index. Common recourse to address environmental concerns is through green education and sustainable practices. However, recent studies reflect the predicaments to implement environmental ideas and policies especially in school settings. In schools, proper understanding of the social dynamics, local context, habits, and pedagogical situation of learning the praxis of sustainability are essential to push for a sustainable and environmental agenda. This paper aims to derive pedagogical imperatives from the lived experiences of basic education teachers who are practitioners or enthusiasts of a sustainable lifestyle in the Philippines' National Capital Region (NCR). The study explores perspectives and habits of a sustainable lifestyle from a schoolteacher's lens by identifying real life situations, individual transformations, and opportunities and challenges. The study provides local context and locates sustainable lifestyle among Filipino teachers. From the respondents' vast repertoire of praxis, the Pedagogical Imperatives on Sustainable Lifestyle (PISL), a set of pedagogical essentials, was derived to serve as a reference guide for schools' implementation of sustainable lifestyle.